2018
DOI: 10.1111/add.14234
|View full text |Cite
|
Sign up to set email alerts
|

Global statistics on alcohol, tobacco and illicit drug use: 2017 status report

Abstract: In 2015 alcohol use and tobacco smoking use between them cost the human population more than a quarter of a billion disability-adjusted life years, with illicit drugs costing further tens of millions. Europeans suffered proportionately more, but in absolute terms the mortality rate was greatest in low- and middle-income countries with large populations and where the quality of data was more limited. Better standardized and rigorous methods for data collection, collation and reporting are needed to assess more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
530
3
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 821 publications
(566 citation statements)
references
References 30 publications
11
530
3
22
Order By: Relevance
“…Abuse and dependence of substances comprise some of the most globally prevalent disorders today [1]. However, our understanding of the fundamental mechanisms underlying drug abuse and dependence remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Abuse and dependence of substances comprise some of the most globally prevalent disorders today [1]. However, our understanding of the fundamental mechanisms underlying drug abuse and dependence remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over 100 million people have already died from smoking cigarettes (Asma et al., ), and this number is expected to increase at a rate of 8 million people every year by 2030 (see Current Protocols article: Gellner, Reynaga, & Leslie, ). Smoking tobacco is the primary factor for disease burden in North America and Western Europe (Peacock et al., ). Smoking is also associated with several major diseases, including over ten types of cancer (Gressard et al., ; Scott Budinger et al., ), chronic obstructive pulmonary disease (Gupta et al., ), heart disease, stroke, asthma (Benjamin et al., ), infertility, premature and low birth‐weight births (Assouni Mindjah, Essiben, Foumane, Dohbit, & Mboudou, ), diabetes (Effoe et al., ), cataracts, age‐related macular degeneration (Velilla et al., ), and periodontal disease (César Neto, Rosa, Pannuti, & Romito, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over 100 million people have already died from smoking cigarettes (Asma et al, 2014), and this number is expected to increase at a rate of 8 million people every year by 2030 (see Current Protocols article: Gellner, Reynaga, & Leslie, 2016). Smoking tobacco is the primary factor for disease burden in North America and Western Europe (Peacock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ordinarily, typical opioid addiction and new psychoactive substance abuse lead to a chronic and relapsing disease that is characterized by a strong desire for opioid usage, increased tolerance, and withdrawal syndrome. The latest global report showed that opioid and new psychoactive substance dependence was one of the most common types of illicit drug dependence, affecting more than 30 million adults aged 15 to 64 years globally. Opioid dependence is directly associated with an increase in major public health issues, including infectious diseases, lack of social duty, economic functioning, and drug‐related crimes .…”
Section: Introductionmentioning
confidence: 99%